Spectral scaling and quantum critical behaviour in the pseudogap Anderson model - Glossop, M; Logan, D (2003)
The pseudogap Anderson impurity model provides a classic example of an essentially local quantum phase transition. Here we study its single-particle dynamics in the vicinity of the symmetric quantum critical point (QCP) separating generalized Fermi-liquid and local-moment phases, via the local-moment approach. Both phases are shown to be characterized by a low-energy scale that vanishes at the QCP; and the universal scaling spectra, on all energy scales, are obtained analytically. The spectrum precisely at the QCP is also obtained; its form showing clearly the non-Fermi-liquid, interacting nature of the fixed point.